The Effect Of Liquid Organic Fertilizer Application On The Growth Of Biograss (Pennisetum purpureum cv. Biograss) - Muhammad, farhan; Media Agus Kurniawan (Universitas Negeri Medan, 2025)
One of the superior varieties developed by the Agricultural Biotechnology and Genetic Resources Research and Development Center (BBPSI Biogen) is the Biograss Agrinak elephant grass. This grass was released as a superior forage crop variety in 2021 and has an impressive yield potential of 319 tons/hectare/year. This study aims to analyze the effect of liquid organic fertilizer application on the growth and productivity of Biograss elephant grass (Pennisetum purpureum cv. biograss) as livestock feed. The research method used a Completely Randomized Design (CRD) with a non-factorial arrangement consisting of 4 treatments and 5 replications. The parameters observed in this study included leaf width, leaf length, plant height, and fresh yield of odot grass. The results showed that treatment P3 resulted in the highest increases in leaf width (3.44 cm), leaf length (62.10 cm), plant height (90.19 cm), and fresh yield of odot grass (687.5 grams), with significant differences compared to other treatments. Application of liquid organic fertilizer at a dose of 15 ml per 1 liter of water gave the best results and has the potential to be applied on a larger scale.